Elucidating the possible mechanism of renal dysfunction in alpha thalassaemia: a review - Nor Aziz Hashim, Nurul Aiman Farhana; Lai, Mei I. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Recent improvement in the treatment and management of α-thalassaemia has enabled patients to live longer and have better quality of life, thus revealing other complications related to the disorder mainly due to the effects of chronic ineffective erythropoiesis and iron overload. We review the renal dysfunction seen in α-thalassaemia as it has been reported (published and personal communication) that the complications presented are more severe than those found in β-thalassaemia patients of similar severity clinically. This review aims to shed light on emerging complications that are currently faced by α-thalassaemia patients as they progress further in life.